The interaction of the structural elements of cultural creative being - Volodymyr Fed (Cхід, 2013)
In the article there is analyzed the problem of the definition of the structural elements of cultural creative being and it is also learned their interaction. In the view of the different schemes there is introduced the author's understanding of the models of interaction of the primary elements of cultural creative being (Man - Nature - Culture), in particular historic, modern and "productive". There is viewed on the scheme of interaction of the worldoutlooking paradigms and traditions, different types of activity and etc.